Anxiety of myoma patients: results of standardized interviews with the State Trait Anxiety Inventory and the Kessler 10 questionnaire. (2nd April 2020) - Knudsen, Nina Isabelle; Richter, Rolf; Kentenich, Heribert; Sehouli, Jalid; David, Matthias
Abstract: Introduction: The aim of this study was to explore a possible relation between myoma-related anxieties and general state or trait anxiety or psychological distress, to get a better understanding of the impact of anxiety on the patients. Methods: This prospective study was conducted at the myoma clinic of a large university hospital in a major European city from November 2016 to February 2017. Patients completed standardized questionnaires on myoma-related fears, the State Trait Anxiety Inventory (STAI), and the Kessler 10. Results: Eighty-five out of 88 women agreed to participate. State-anxiety on the STAI had a mean of 49.4 (11 points above the norm ( p  < .001)), and trait-anxiety had a mean of 42.0 (5 points above the norm ( p  = .001)). Thirty-seven percent of the patients had distress values on the K10 above the norm (defined as <20). More myoma-related fears correlated with higher scores on the Kessler and STAI. The scores were not related to the level of information about myomas or duration of illness. Conclusions: Myoma-related fears correlated with higher mental distress and elevated state and trait anxiety levels. Thus, physicians can contribute to the overall well-being of patients when they relieve them of the myoma-related anxiety. Further research is needed to determine whether treatment has any impact on anxiety or mental distress.